Pengaruh Struktur Modal dan Pertumbuhan Perusahaan terhadap Potensi Financial Distress - Dewi Putri Indriasari; Seftira; Nurdjanna Fadjrin Uluputty; Ambo Rappe (Management and Accounting Research Journal, 2025)
The Influence of Capital Structure and Company Growth on the Potential for Financial Distress at PT. Magatti Internasional. This study aims to analyze the influence of capital structure and business growth on the potential for financial distress at PT. Magatti Internasional during the period 2020 to 2023. Capital structure is measured using the Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR), while business growth is analyzed through the growth of the company's revenue and assets. The data used in this study were obtained from the company's annual financial reports which were analyzed using quantitative analysis methods, with the help of SPSS software to test the significance of the influence of these variables on financial distress. The results of the study indicate that capital structure and business growth do not have a significant effect on the company's financial distress. This study suggests that companies optimize the management of capital structure and business growth by paying more attention to quality aspects than quantity, as well as improving financial monitoring and risk management to reduce the potential for financial distress.